Teacher’s understanding of teaching models and students’ human literacy - Titik Ulfatun; Suyatmini Suyatmini; Arnida Kusumaningtyas; Yovi Annang Setiyawan (Institute of Advanced Engineering and Science, 2023)
The strengthening of students’ human literacy can be done through appropriate learning processes and models of teaching. The purpose of this study is to explore teachers’ understanding of models of teaching and whether the applied models can strengthen students’ human literacy. This qualitative case study of two vocational high schools in Surakarta used semi-structured interviews and documentation for data collection purposes. The results of this study found that teachers have an unsuitable understanding of models of teaching employed in Basic Accounting subject. In the interviews, the respondents of this study explained the types of learning media used (PowerPoint, Zoom, recordings, WhatsApp Group, and Quizizz) and methods of teaching (lectures and assignments), instead of models of teaching (discovery learning, inquiry-based learning, project-based learning, and problem-based learning). Even though the lesson plans they compiled have mentioned models of teaching, teachers felt that these models were not sufficient to strengthen students’ human literacy. These findings can help teachers to revisit the models of teaching used in the classroom with a proper understanding. Teachers are advised to improve their understanding of concepts related to teaching and learning activities. In addition, it is highly necessary for teachers to apply different models of teaching to strengthen students’ human literacy.